RELEVANCE CONCEPT OF ‘MERDEKA BELAJAR’ IN MUHAMMADIYAH PERSPECTIVE OF PROGRESSED ISLAMIC EDUCATION - Pudyas Tataquna Raniya; Farid Setiawan (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This study aims to analyze the relevance of the concept of merdeka belajar in progressive Islamic education from the Muhammadiyah perspective. This is motivated by the condition of teachers who are too preoccupied with administration so they lack focus on developing student potential. Added to this, the Program for International Student Assessment (PISA) research conducted in 2019 said that student assessment in Indonesia was in 6th place from the bottom. Indonesia occupies the 74th position out of 79 countries. So, to overcome these problems the government held merdeka belajar which aims to optimize students' potential, and see the suitability of free learning education with the concept of progressive Islamic education according to Muhammadiyah. Researchers used library research methods (library research). Data collection techniques by collecting sources, books, journals, and previous research. The results of the study show that there is relevance to the concept of merdeka belajar with KH's statement. Ahmad Dahlan that with the development of the times, education must be able to keep up, so this is where good education is called if it is able to adapt to the demands of the times and modernity. Because in fact, progressive Islamic education is education that implements a modern education system and is able to prevent stagnation of thought.